Komparasi Studi Historis-Kritis Al-Qur’an Orientalis (Studi Pemikiran Abraham Geiger, Theodor Nöldeke dan Angelica Neuwirth) - Nur, Zunaidi; Iballa, Dona Kahfi Ma; Azima, Muhammad Fauzhan (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
One of the controversial topics in orientalist studies of the Qur'an is about the similarity of the Qur'an with previous books, especially the Bible. Some orientalists armed with a historical-critical approach produce diverse conclusions regarding the similarity of the Qur'an with the previous book. This study aims to describe the main thoughts of three orientalists, namely Abraham Geiger, Theodor Noldeke, and Angelika Neuwirth regarding the Qur'an through a comparative study. This research is a qualitative research that combines three consecutive methods, namely exploration, explanation, and description-analysis. The result of this study is that although the three orientalists use the same methodology, each orientalist has a different conclusion due to differences in interpretation among the three. In the historical-critical study of the Qur'an, the difference in conclusions between Geiger, Noldeke, and Neuwirth occurs because of the difference in their views of the “blind spot” that causes similarities between the Qur'an and the Bible. Geiger argues that this shows Muhammad's adoption of a unified Arab society. Noldeke sees the difference due to Muhammad's ignorance of valid information, because Muhammad only got oral information and did not refer to the Bible as a primary reference. Meanwhile, Neuwirth argues that this difference actually shows the form of interaction between the Qur'an and the Bible.